Comprehensive physiotherapy management in covid-19 – a narrative review - Kalirathinam, Deivendran; Guruchandran, Raj; Subramani, Prabhakar (Scientia Medica, 2020)
The 2019 novel coronavirus officially named as coronavirus disease 2019 (COVID-19) pandemic by the World Health Organization, has spread to more than 180 countries. The ongoing global pandemic of severe acute respiratory syndrome coronavirus, which causes COVID-19, spread to the United Kingdom (UK) in January 2020. Transmission within the UK was confirmed in February, leading to an epidemic with a rapid increase in cases in March. As on April 25- 2020, there have been 148,377 confirmed cases of COVID-19 in the UK and 20,319 people with confirmed infection have died. Survival of critically ill patients is frequently associated with significant functional impairment and reduced health-related quality of life. Early physiotherapy and community rehabilitation of COVID-19 patients has recently been identified as an essential therapeutic tool and has become a crucial evidence-based component in the management of these patients. This comprehensive narrative review aims to describe recent progress in the application of physiotherapy management in COVID 19 patients. Assessment and evidence- based treatment of these patients should include prevention, reduction of adverse consequences in immobilization, and long-term impairment sequelae. A variety of techniques and modalities of early physiotherapy in intensive care unit are suggested by clinical research. They should be applied according to the stage of the disease, comorbidities, and patient’s level of cooperation. ***Tratamento fisioterápico na covid-19 - uma revisão narrativa*** O novo coronavírus de 2019 oficialmente nomeado como pandemia da doença por coronavírus 2019 (COVID-19) pela Organização Mundial de Saúde, se espalhou para mais de 180 países. A pandemia global em curso da síndrome respiratória aguda grave causada pela COVID-19, se espalhou para o Reino Unido em janeiro de 2020. A transmissão no Reino Unido foi confirmada em fevereiro, levando a um rápido aumento de casos em março. Em 25 de abril de 2020, houve 148.377 casos confirmados de COVID-19 no Reino Unido e 20.319 pessoas, com infecção confirmada, morreram. A sobrevivência de pacientes críticos está frequentemente associada ao comprometimento funcional significativo e redução da qualidade de vida relacionada à saúde. A fisioterapia precoce e a reabilitação comunitária de pacientes com COVID-19 foram recentemente identificadas como uma ferramenta terapêutica essencial e tornaram-se um componente crucial baseado em evidências no tratamento desses pacientes. Esta revisão abrangente tem como objetivo descrever o progresso recente na aplicação do manejo da fisioterapia em pacientes com COVID-19. A avaliação e o tratamento baseado em evidências desses pacientes devem incluir a prevenção, a redução de consequências adversas da imobilização e as sequelas de comprometimento a longo prazo. Uma variedade de técnicas e modalidades de fisioterapia precoce em unidade de terapia intensiva são sugeridas por pesquisas clínicas. Eles devem ser aplicados de acordo com o estágio da doença, com as comorbidades e com o nível de cooperação do paciente. Palavras-chave: COVID-19; terapia física; reabilitação hospitalar e comunitária.